Advances in microbial physiology. - Rose, A. H. (Advances in microbial physiology, 1993)
This research level review series covers diverse aspects of microbial physiology and biochemistry, including: inositol metabolism in yeasts, bacterial adhesion, organic acids, the bacterial flagellum, mechanical behaviour of bacterial cell walls.